2013
DOI: 10.1590/s0100-83582013000100013
|View full text |Cite
|
Sign up to set email alerts
|

Variação do tamanho de sementes de plantas daninhas e sua influência nos padrões de emergência das plântulas

Abstract: Estudos relacionados ao tamanho de sementes e sua influência no processo germinativo de plantas daninhas são necessários devido à grande importância das espécies e à escassez de informações relacionadas à produção de sementes dessas plantas. Dessa forma, este trabalho objetivou estudar a variação do tamanho de sementes de 12 espécies de plantas daninhas e a emergência de duas dessas espécies semeadas em diferentes profundidades. Foi mensurado o peso unitário de 200 sementes por espécie de planta daninha seleci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(8 reference statements)
0
8
0
1
Order By: Relevance
“…decumbens emergence was affected by seeds location at the soil profile, therewith has occurred high intensity emergence reduction from 7.0 cm depth. Araldi et al (2013) and Ikeda et al (2013), also observed that sowing depth (B. decumbens) from 0.0 to 6.0 cm obtained the highest SEI.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…decumbens emergence was affected by seeds location at the soil profile, therewith has occurred high intensity emergence reduction from 7.0 cm depth. Araldi et al (2013) and Ikeda et al (2013), also observed that sowing depth (B. decumbens) from 0.0 to 6.0 cm obtained the highest SEI.…”
Section: Resultsmentioning
confidence: 73%
“…Araldi et al (2013), evaluated accumulated emergence at sowing depths and observed resemblances between three seed classification sizes (small, medium and big).…”
Section: Resultsmentioning
confidence: 99%
“…Measures of position, mean, median and mode are different among them, and mean and median values are higher than mode values; therefore, this asymmetrical distribution is positive (Table 3). Thus, it is possible to identify that there is higher variability among higher ammonium contents, compared to lower ones, in the frequency distribution curve; curves tend to quickly go up and then go down in a slower way (Araldi et al, 2013). This behavior is verified in Figure 1B, with the first derivation of Gompertz model.…”
mentioning
confidence: 57%
“…The position, mean, median, and mode data measurements were different from each other, and the mean and median values were higher than the modal value. This positive asymmetric distribution (Table 2) enables the identification of greater variability between the higher levels of ammonia versus the lower levels in the frequency distribution curve, with the curves tending to rise rapidly and fall more slowly (ARALDI et al, 2013). This performance is also shown in Figure 3, with the first derivative of the Gompertz model.…”
Section: Study Of Wandering Jew Plant Sensitivity To Glufosinate Ammomentioning
confidence: 75%